Analisis Hubungan Antara Kualitas Air Bersih dengan Kejadian Diare pada Balita - Sitatul Hajah Fatimah; Andriyani Andriyani; Suherman Jaksa (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Diarrhea is an infectious disease caused by complex environmental conditions and is experienced by every country in the world. Diarrhea is an endemic disease that can become an Extraordinary Event (KLB) in Indonesia which often causes death. This study analyzed the relationship of clean water quality to the incidence of diarrhea. The method of analysis used was literature review. This study used 15 journals taken from the last 5 years with Google Scholar and PubMed data sources. The implementation of the study began in April-May 2025. Based on the literature review, it was found that there is a significant relationship between clean water sources and the level of diarrhea cases in the community. This indicates that E. coli contamination of consumed water increases the likelihood of diarrhea, especially in children under five. The results of this study are expected to provide an overview of how the government and health workers control diarrhea cases in Indonesia.